Functional genomics identifies a requirement of pre‐mRNA splicing factors for sister chromatid cohesion. (25th September 2014) - Sundaramoorthy, Sriramkumar; Vázquez‐Novelle, María Dolores; Lekomtsev, Sergey; Howell, Michael; Petronczki, Mark
Abstract Sister chromatid cohesion mediated by the cohesin complex is essential for chromosome segregation during cell division. Using functional genomic screening, we identify a set of 26 pre‐mRNA splicing factors that are required for sister chromatid cohesion in human cells. Loss of spliceosome subunits increases the dissociation rate of cohesin from chromatin and abrogates cohesion after DNA replication, ultimately causing mitotic catastrophe. Depletion of splicing factors causes defective processing of the pre‐mRNA encoding sororin, a factor required for the stable association of cohesin with chromatin, and an associated reduction of sororin protein level. Expression of an intronless version of sororin and depletion of the cohesin release protein WAPL suppress the cohesion defect in cells lacking splicing factors. We propose that spliceosome components contribute to sister chromatid cohesion and mitotic chromosome segregation through splicing of sororin pre‐mRNA. Our results highlight the loss of cohesion as an early cellular consequence of compromised splicing. This may have clinical implications because SF3B1, a splicing factor that we identify to be essential for cohesion, is recurrently mutated in chronic lymphocytic leukaemia.